1984
DOI: 10.1111/j.1365-2125.1984.tb02477.x
|View full text |Cite
|
Sign up to set email alerts
|

The short term effects of bezafibrate on the hypertriglyceridaemia of moderate to severe uraemia.

Abstract: Hypertriglyceridaemia, an atherogenic risk factor, is a well recognised complication of uraemia, and is present in the earliest stages of the disease. Bezafibrate is an effective hypolipidaemic agent, and its effect in moderate to severe uraemia is documented in this study. Significant reductions in serum triglyceride and cholesterol have been achieved after 1 month's therapy with a reduced dosage of bezafibrate. A reduction in the hyperinsulinaemia was also seen, but no change in the fractional removal rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…20 The result of the present study was consistent with that of this study. In the FIELD study, creatinine levels were significantly lower in the fenofibrate group than in the placebo group at 8 weeks after withdrawal of study drugs and it was suggested that fenofibrate had renoprotective effect in conjunction with the effect on albuminuria.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…20 The result of the present study was consistent with that of this study. In the FIELD study, creatinine levels were significantly lower in the fenofibrate group than in the placebo group at 8 weeks after withdrawal of study drugs and it was suggested that fenofibrate had renoprotective effect in conjunction with the effect on albuminuria.…”
Section: Discussionsupporting
confidence: 83%
“…19 Previous studies have reported that creatinine levels decreased after stopping fenofibrate. 19,20 However, it is unclear whether the reversibility is complete or partial.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of bezafibrate in uraemic patients not yet receiving dialy sis [6,7] or maintained on haemodialysis [5] has been reported, our study is unique in three aspects: (1) we have included only CAPD patients; (2) we have used bezafi brate in its sustained-release form. Given at 400 mg/day, the drug caused severe toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemic heart disease still claims many lives on dialysis [2]. High-density lipoprotein cholesterol (HDL-C), thought to be protective against atherogenesis [3], is markedly reduced in uraemic patients and in those on continuous ambulatory peritoneal dialysis [4] (CAPD) [1], The Helsinki Heart Study [4] has shown that a reduction of ischaemic heart events during treatment with gemfi brozil is associated with an increase in serum HDL-C. Bezafibrate, a clofibric acid derivative, has been shown to increase HDL-C in uraemic patients [5][6][7]. A sustainedrelease form of the drug is now available, and the follow ing article describes an open study of the effect of sus tained-release bezafibrate on lipid metabolism in CAPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome occurred in subjects with normal as well as impaired kidney function [5,6], Pharmacokinetic investi gations of bezafibrate in patients with chronic uremia showed that the half-life is significantly prolonged and renal clearance is markedly decreased [7], On the basis of these data, a dose adjustment has been suggested in patients with renal impairment. However, a significant increase in serum C K values, followed by reversion after drug withdrawal, has been reported despite the use of reduced dosages [8].…”
Section: Introductionmentioning
confidence: 99%